Define x* by the equation x* = π – x. Then ((–π)*)* =

(A) –2π (B) –1 (C) –π (D) 2π (E) 4π

Answer: ((–π)*)* = (π – (–π))* = (π + π)* = (2π)* = π – 2π = –π. Choice C

could someone make sense of this for me?

Printable View

- Dec 5th 2008, 05:16 PM~berserkDefined Functions
Define x* by the equation x* = π – x. Then ((–π)*)* =

(A) –2π (B) –1 (C) –π (D) 2π (E) 4π

Answer: ((–π)*)* = (π – (–π))* = (π + π)* = (2π)* = π – 2π = –π. Choice C

could someone make sense of this for me? - Dec 5th 2008, 05:37 PMsastry.somayajulaWill the below solution makes sense?
It has been given that x* = π – x

lets say -n = x

then (-n)* = n - (-n) = 2n

then ((-n)*)* = (2n)* = n - 2n = -n